2021
DOI: 10.3389/fpsyg.2021.585128
|View full text |Cite
|
Sign up to set email alerts
|

The Contagion of Donation Behaviors Changes Along With the Abatement of the COVID-19 Pandemic: An Intertemporal Survey Experiment

Abstract: We conducted an intertemporal online experiment to examine the contagion of others’ positive and negative donation behaviors. We collected two sets of data during and after the peak of the COVID-19 pandemic in China. The participants donated to the charitable fund, “Against COVID-19, The China Charity Federation Is on the Move.” We further investigated the mediating effect of social anxiety on the link between the contagion of donation behaviors and the changes in the COVID-19 situation. A total of 1022 partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Subjects in China that were more intensively exposed to the Covid-19 crisis reveal more antisocial behavior than those with lower exposure (Lohmann et al, 2020). Li et al (2021) conducted an online experiment to examine the contagion of others' positive and negative donation behavior of the Covid-19 pandemic in China during and after the peak. They also investigated the impact of social anxiety on the link between the contagion of donation behaviors and the changes in the Covid-19 situation.…”
Section: Related Literaturementioning
confidence: 99%
“…Subjects in China that were more intensively exposed to the Covid-19 crisis reveal more antisocial behavior than those with lower exposure (Lohmann et al, 2020). Li et al (2021) conducted an online experiment to examine the contagion of others' positive and negative donation behavior of the Covid-19 pandemic in China during and after the peak. They also investigated the impact of social anxiety on the link between the contagion of donation behaviors and the changes in the Covid-19 situation.…”
Section: Related Literaturementioning
confidence: 99%
“…During the pandemic's peak, positive donation behavior demonstrated by others was more likely to influence participants' initial decisions. However, such differences disappeared after the peak since the spread of positive donation behavior and social anxiety significantly decreased along with the abatement of the pandemic (Li et al, 2021 ). This aligns with research that found social responsibility guilt enhances the sense of responsibility in an individual to donate (Basil et al, 2007 ).…”
Section: Financial Behavior and The Nonprofit Industrymentioning
confidence: 99%
“…However, the conclusions regarding the positive or negative impacts of information on donation behaviors are not consistent. Many prior studies show that information about the previous donation amounts increases individuals' donation amounts (Shang et al, 2007 ; Martin and Randal, 2008 ; Shang and Croson, 2009 ; Smith et al, 2015 ; Goeschl et al, 2018 ; Vesely and Klöckner, 2018 ; van Teunenbroek and Bekkers, 2020 ; Drouvelis and Marx, 2021 ; Li et al, 2021 ; van Teunenbroek et al, 2021 ). There are also several studies drawing different conclusions and showing a negative effect (Croson and Shang, 2008 , 2013 ; Meyer and Yang, 2016 ; Kubo et al, 2018 ); or no effect (Murphy et al, 2015 ) of several types of social information on donation amounts under certain situations.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Many social context-related factors impact donors' psychological states and behaviors (Ferguson et al, 2015 ; Braun, 2017 ). Li et al ( 2021 ) suggest that participants' social anxiety decreased along with the abatement of the pandemic and that social anxiety completely mediated the relationship between pandemic abatement and the decrease in the contagion of positive donation behaviors. By comparing COVID-19-related campaigns and non-COVID-19-related campaigns, Saleh et al ( 2021 ) suggest that COVID-19-related campaigns raised more money, had a longer narrative description, and were more likely to be shared on Facebook than other campaigns in the study period.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%